2017
DOI: 10.5455/njppp.2017.7.0305804052017
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, open-label, comparative study of efficacy of low-dose continuous versus low-dose intermittent oral isotretinoin therapy in moderate-to-severe acne vulgaris

Abstract: Background: Acne vulgaris is a chronic inflammatory disease of pilosebaceous units. Oral isotretinoin is recommended for patients with moderate-to-severe acne vulgaris who are not responding satisfactorily to conventional therapies. Recent reports indicate that acne patients have been benefiting from the low-dose treatment protocols. Aims and Objectives: The aim of this study was to assess and compare the efficacy of oral isotretinoin in low-dose continuous and intermittent treatment of moderate-to-severe acne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“… 40 It was approved for severe acne (conglobata and nodular-cystic), but evidence demonstrated in controlled randomized clinical trials (CRCTs) since 1980, in systematic reviews (SRs), consensuses, and recommendations of dermatology societies allowed to expand the indication for nodular-cystic and moderate papulopustular forms resistant to other treatments, with tendency to scarring, and emotional and social functional impairment. 1 , 2 , 36 , 38 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 A single course of the drug leads to cure in two-thirds of patients. Recurrences may take place, but they are milder and manageable with topical treatments.…”
Section: Resultsmentioning
confidence: 99%
“… 40 It was approved for severe acne (conglobata and nodular-cystic), but evidence demonstrated in controlled randomized clinical trials (CRCTs) since 1980, in systematic reviews (SRs), consensuses, and recommendations of dermatology societies allowed to expand the indication for nodular-cystic and moderate papulopustular forms resistant to other treatments, with tendency to scarring, and emotional and social functional impairment. 1 , 2 , 36 , 38 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 A single course of the drug leads to cure in two-thirds of patients. Recurrences may take place, but they are milder and manageable with topical treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Severe acne patients may be refractory to response, in particular, on lower doses. Five studies in the analysis included patients known to have mild-to-moderate acne, 21,[25][26][27]29 whereas severe acne patients in the other five studies 17,[22][23][24]28 was not excluded. Additionally, previous evidence has shown that acne patients with hormonal abnormalities or who take medications known to induce acne often respond differently to isotretinoin.…”
Section: F I G U R E 1 Study Flow Diagrammentioning
confidence: 99%
“…Study participants were followed during the treatment period for 6-8 months, [21][22][23][24][25][26][27] but the length of follow-up in three studies was only 4 months. 17,25,28 Study participants were followed after the end of the treatment for 6-12 months, 21,23,24,28,29 the length of the follow-up on the other hand, in three studies was only 2-3 months 17,22,26 and in two studies 25,27 they did not follow the participants up post-treatment. However, because it was clinically meaningful, relapse was investigated as a secondary meta-analytic outcome.…”
Section: F I G U R E 1 Study Flow Diagrammentioning
confidence: 99%
“…Initially, isotretinoin is only indicated for nodulocystic AV cases. However, it is recently used for moderate to severe AV that does not respond well to topical combination therapy or systemic antibiotics [24]. Table 3 outlines some of the results from clinical trials of isotretinoin.…”
Section: Effectiveness Of Av Therapy With Isotretinoinmentioning
confidence: 99%
“…Prior to therapy, assessments include liver function tests, fasted lipid profile (including triglyceride level), blood glucose, creatinine, and complete blood count with differential counts. Screening for mood changes, psychosis, aggression, suicidal thoughts, skin changes, and visual changes can also be conducted prior to therapy [23,24].…”
Section: Side Effects and Monitoringmentioning
confidence: 99%